From crops to clinic: the impact of dual azole use on antifungal resistance in Candida and Candida associated yeasts - Allison, Jessica C.; Hyland, Edel M. (Frontiers in Microbiology, 2025)
Invasive fungal infections caused by pathogenic yeasts are an escalating global health crisis that demands urgent attention within a One Health framework. This review critically examines mounting evidence that widespread agricultural azole fungicide use is a key driver accelerating antifungal resistance in pathogenic yeast. We dissect the shared molecular targets and resistance pathways that underpin dangerous cross-resistance between environmental fungicides and clinical azoles. Traditionally viewed as human commensals, we provide a comprehensive account of the evidenced environmental reservoirs of yeast pathogens, including agricultural soils, wastewater, and the food chain. Ecosystems burdened by persistent azole contamination that create hotspots for resistance evolution and amplification. With antifungal treatment options rapidly diminishing and resistant infections causing rising morbidity and mortality worldwide, we identify vulnerabilities in our shared environment and consider integrated surveillance, stewardship, and environmental interventions to help preserve the efficacy of life-saving antifungals and mitigate the growing threat of fungal disease.